2019
DOI: 10.1108/ijmhsc-01-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Transnational marriages and the health and well-being of Thai migrant women living in Norway

Abstract: Purpose The purpose of this paper is to investigate the health and well-being of Thai immigrant women in transnational marriages. Design/methodology/approach Interviews with 13 Thai women living in Norway who have (had) a Norwegian spouse/partner were conducted and the transcripts were analysed using thematic analysis. Findings Initial culture shock and a mixture of employment issues, transnational ties, marital relationships and social networks intertwined to influence women’s health and well-being over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…This dynamic, engagement with the arrival country and maintenance of cultural ties, provides the opportunity to essentially live in two spaces. Thai migrant women often have difficulty finding suitable and long-term full time employment in Norway and this may lead some women to draw upon their networks to establish their own businesses and create their own employment opportunity [15, 16]. Massage shops and restaurants, owned by Thai migrants, are locales where women navigate sexualized stereotypes about Thai women, develop strategies to maintain their own safety and vie to be acknowledged as legitimate business persons [17, 18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This dynamic, engagement with the arrival country and maintenance of cultural ties, provides the opportunity to essentially live in two spaces. Thai migrant women often have difficulty finding suitable and long-term full time employment in Norway and this may lead some women to draw upon their networks to establish their own businesses and create their own employment opportunity [15, 16]. Massage shops and restaurants, owned by Thai migrants, are locales where women navigate sexualized stereotypes about Thai women, develop strategies to maintain their own safety and vie to be acknowledged as legitimate business persons [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…However, Thai women who used an interpreter were more likely to receive counselling and specialist referral than those who did not [19]. In another qualitative study of Thai migrant women we found that some women can struggle to juggle the demands of their life in Norway and their roles as breadwinners, wives, and mothers with children in Thailand which can have a negative effect on health and wellbeing [16]. A non-governmental organisation (NGO) report found that Thai women are among the highest overnight migrant users of emergency shelters, which implies that Intimate Partner Violence (IPV) may be a challenge [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outreach through Thai networks, could improve Thai migrants’ knowledge of the Norwegian healthcare system. The strength of Thai networks as information sources has been documented by another Norwegian study and a network approach to disseminate information appears warranted [6, 30]. Providing more health systems information in the fifty-hour training course that marriage migrants take when they arrive in Norway could also help reach this group.…”
Section: Discussionmentioning
confidence: 99%
“…All of these could lead to expected or unanticipated outcomes in the marriages and family lives. While there is a significant amount of research on how transnational marriage has shaped family relations, including imbalance of husband-wife power, division of labor within the household, marital satisfaction or dissatisfaction, risks, vulnerabilities, tensions, abuses, termination of marriage, and even health problems (e.g., Charsley 2005;Freeman 2005;Ko 2012;Kudo 2016;Straiton et al 2019;Wang 2007), the impact of transnational marriage on lineage remains a blank spot.…”
Section: Transnational Marriagementioning
confidence: 99%